Polish Power: A Community's Reaction to the Great Migration and the Fair Housing Act of 1968 - Saksefski, Caroline (My University, 2017)
The South Side of Milwaukee, Wisconsin had been deemed Polish since the 1850s. When they arrived from Europe, the Poles were seen as second class white in the primarily German city and forced to live in a specific area. They showed little resistance and came to call the area Little Polonia. It was their new found country within the United States, a safe place. It would not be until 1945, when the Poles began to feel threatened by the influx of rural Black Southerners would move to the North Side of Milwaukee. They saw this new community as thieves against their economic and social position. So the white communities enacted similar policies to the Jim Crow South, separating: schools, factories and playgrounds. Although, the Polish had accepted their standing and the territory that came with it, but the Black community become restless and fought for the freedoms that they had earned long ago. Through Census surveys, newspaper articles and ethno mapping, to pursue an explanation of strong racial tensions in Milwaukee resulting in a riot and over 200 marches for open housing in the summer of 1967.
Keywords: Milwaukee (Wis.)--Emigration and immigration; African Americans--Wisconsin--Milwaukee; Little Polonia (Milwaukee, Wis.); African Americans--Wisconsin--Milwaukee--Social conditions; Polish Americans--Wisconsin--Milwaukee--Social conditions; Civil rights movements--Wisconsin--Milwaukee--History--20th century